THE EFFECT OF PEER REVIEW ON EFL STUDENTS’ WRITING SKILL IN WRITING “NURSING CARE DOCUMENTATION - Husna, Arina Hafadhotul (Universitas Nusantara PGRI Kediri, 2017)
This study concerns on the effect of peer review on EFL students’ writing skill in writing nursing care documentation. The aims of this study are to investigate the possible effectiveness of the peer review technique to increase the quality of nursing students’ writing skill and to see whether this method motivates student to write. The method of the study is quantitative method. The participants were 78 nursing students in the fourth semester of CendekiaUtama Health College. They were randomly categorized into two experimental and control groups. In the experimental group were providing with an additional peer review instruction offered by O’Muirheartaigh (1990) including the provision of constructive feedback to their peers and evaluating and correcting the peer’s performances. They were paired for peer review, conferencing and exchanging their Nursing care documentation with those of their peers. The reviewers had to correct, evaluate and respond those Nursing care documentation. While, in the control group were traditionally handled by teacher who assigned them homework and correct their Nursing care documentation by themselves.The experiment was run over two month. The data were collected using questionnaire, pre – test and post – test for language proficiency and writing skill, peer response sheet, writing criteria and guidelines sheet. The result of the study indicated that p-score is 0,000 <0,05, So that Ho is Rejected and Ha is Accepted which means there is difference of Pre Test with Post Test score. It is known that statistic t - arithmetic is -6.202 which means the score of pre - test is smaller than post - test with point score 6.202. It indicated that the writing of the students in the experimental group improved more than those in control group. Also, those engaged in peer review method were motivated to write more and enjoy writing. It was concluded that peer review provides learners with an authentic audience, increase the students’ motivation for writing and enables them to receive different views on their writing. Keywords: Peer Review, EFL Students, Writing Improvement, Nursing care documentation